Gaba Transaminase Deficiency Presenting as Neonatal Encephalopathy - Amira, Oshi; Abdullah, Alfaifi; Mohammed, Z. Seidahmed; Khalid, Al Hussein; Abeer, Miqdad; Abdelmohsin, Samadi; Omar, Abdelbasit (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Gama-aminobutyric (GABA) transaminase deficiency is a rare disorder with only few cases described in the literature. We present here a neonate who presented early with an epileptic encephalopathy. The recently described diagnostic criteria and gene sequencing are now the backbone for diagnosing this severe rare metabolic encephalopathy and has helped in understanding its metabolic effects and the pathophysiology. Affected families can benefit from genetic counseling for their future pregnancies. The variant in this baby (p.Gly106Ser) has not been described before.